Harry S. Truman National Historic Landmark District: a neighborhood case study - Steinman, Eva Melinda (Kansas State University, 2012)
In 2011, the United States Secretary of the Interior approved a proposal for expansion of the Harry S. Truman National Historic Landmark District in Independence, Missouri. The expansion of the historic district and the subsequent press resulting from the expansion was the inspiration for this report. The topic area of this report is historic preservation. Historic districts come with increased rules and regulations that can be seen as limiting a resident’s use of the properties within these districts. This report is concerned with the actual condition within a historic district with a central hypothesis that historic districts do have a positive association with property condition. In order to answer the research question, a multiple-case replication explanatory case study was performed using the original landmark district boundaries and two comparable nearby neighborhoods outside of the historic landmark district. The case study utilized secondary sources and in-field observations to analyze seven researchable factors about the parcels within the study areas. These factors were compared and contrasted during the cross case analysis. To further the understanding of the study area, a detailed profile of the City of Independence, Missouri, was produced. This profile looked at the historical development of the city, as well as economic and demographic statistics. The theoretical framework behind historic districts was also analyzed for this report. It is beneficial to look at this question in order to evaluate the potential implementation of a historic district that a planner may face in their municipality such as whether historic preservation regulations should be maintained, expanded, or eliminated or a historic district should be put in place. The report ends with a conclusionary chapter including recommendations, lessons for planning professionals, and ideas for further research.
Keywords: Historic preservation; Historic district; Planning; Harry S. Truman; Independence, Missouri; Urban Planning (0999)